1976
DOI: 10.1111/j.1348-0421.1976.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Coryneforms Isolated from Human Bone Marrow and Skin

Abstract: Eighteen isolates of anaerobic coryneforms from human bone marrow and skin and four type strains of Propionibacterium were studied chemically, biochemically and antigenically. All of the isolates were identified as Propionibacterium acnes; of the 18 isolates, 16 belonged to serotype I and two to serotype II. By means of gas liquid chromatography and mass spectral analysis, a large amount of iso-type fatty acids, such as iso-pentadecanoic and iso-heptadecanoic acids were detected in whole cells of isolates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…C15:0 is an FA that is characteristically found as a constituent lipid in P. acnes . Our findings were different than those of Saino et al (1976) [49], who suggested that it was possible to predict that an incremental increase in the amount of P. acnes could lead to worse acne lesions. Even in Groups 1 and 3 (which were treated with lymecycline), an increase in the C15:0 levels from D30 to D90 ( P = 0.006) was observed, which could indicate that pentadecanoic acid is not an important constitutional element for this bacteria or that it is, in fact, a marker of unfeasible (devitalized) bacteria.…”
Section: Discussioncontrasting
confidence: 99%
“…C15:0 is an FA that is characteristically found as a constituent lipid in P. acnes . Our findings were different than those of Saino et al (1976) [49], who suggested that it was possible to predict that an incremental increase in the amount of P. acnes could lead to worse acne lesions. Even in Groups 1 and 3 (which were treated with lymecycline), an increase in the C15:0 levels from D30 to D90 ( P = 0.006) was observed, which could indicate that pentadecanoic acid is not an important constitutional element for this bacteria or that it is, in fact, a marker of unfeasible (devitalized) bacteria.…”
Section: Discussioncontrasting
confidence: 99%
“…Preparation of the phenol-treated cells of P. acne8. The phenol-treated cells of P. acnes C-7 were prepared by the method described in the preceding paper (20). The suspension containing 20 mg (dry weight) of the phenol-treated cells per ml of saline was usually used.…”
Section: Methodsmentioning
confidence: 99%
“…In the preceding paper of the series, chemical, biochemical, and antigenical studies were made on P. acnes isolated from human bone marrow and skin, and it was found that an insoluble middle layer including phenol-treated cells obtained by a hot phenol water extraction was the most effective means for the enhancement of phagocytic activity in mice, as well as for tumor protection and adjuvant action (20). The purpose of the present study is to clarify the characteristics and the mechanism of resistance exerted in mice by the phenol-treated cells of P. acnes against subsequent bacterial infections.…”
mentioning
confidence: 99%
“…Although an abundance of data on biochemical and serological studies of Propionibacterium acnes has been accumulated, there still remains a great deal of confusion regarding criteria for classifying the bacteria, and other species such as P. granulosum are often mistakenly included in the group (1,(9)(10)(11)(12)(13)(14)19).…”
mentioning
confidence: 99%